Effect of Lifestyle on Consumer Decision Making: A Study of Women Consumer of Pakistan - Mohiuddin, Zaeema Asrar (Journal of Accounting, Business and Finance Research, 2018)
To develop the understanding of consumer behavior is considered as an important element for the producers and marketing managers. The buying behavior of consumers is highly dependent on their lifestyle. This research strives to examine the effect of lifestyle on the female buying decisions. For this reason, 150 close ended questionnaires were distributed among the female buyers of Karachi followed by convenient sampling approach. Out of 150, 120 questionnaires were received for the further analysis. The sample portrays that majority of the women belong from the upper middle class. Most of them are working women and students and belong from the age group of 18 years to 50 years. The findings of the study highlights that majority of the women prefer to buy imported brands rather than local ones. In line with this, they prefer to go through the reviews regarding the newly launched brand before making any purchase. With respect to the findings, it is recommended that local producers should improve their quality so that they can capture the large market of female buyers.